ANALISIS PENDAPATAN KELUARGA DAN SANITASI LINGKUNGAN RUMAH TANGGA TERHADAP KEJADIAN STUNTING PADA BALITA DI JAWA TIMUR MENGGUNAKAN REGRESI LOGISTIK - Dewi Kurnia Sari; Yusrina Nur Dianati; Ahisa Novianti (ASSYIFA : Jurnal Ilmu Kesehatan, 2026)
Stunting is a chronic nutritional problem that remains a major public health challenge in Indonesia and has long-term impacts on human resource quality. This study aims to analyze the effect of family income and household environmental sanitation on the incidence of stunting in newborns in East Java. This research employed a quantitative approach with a cross-sectional design. The data consisted of both primary and secondary sources with a total sample of 696 respondents selected using purposive sampling. Data were analyzed using binary logistic regression. The results showed that the model was statistically significant with a classification accuracy of 74.7%. Family income and household sanitation conditions had a significant effect on stunting, while water conditions and sanitation facilities were not significant. Higher family income and better sanitation conditions were associated with a lower risk of stunting in newborns. Therefore, stunting prevention efforts should focus on improving household economic conditions and overall environmental sanitation.